2019
DOI: 10.1002/mc.23001
|View full text |Cite
|
Sign up to set email alerts
|

Junctional adhesion molecule‐A is down‐regulated in anaplastic thyroid carcinomas and reduces cancer cell aggressiveness by modulating p53 and GSK3 α/β pathways

Abstract: Junctional adhesion molecule A (JAM‐A) is a transmembrane protein that contributes to different biological process, including the epithelial to mesenchymal transition (EMT). Through an EMT profiler array, we explored the molecular players associated with human thyroid cancer progression and identified JAM‐A as one of the genes mostly deregulated. The quantitative real‐time polymerase chain reaction and immunohistochemistry analyses showed that downregulation of JAM‐A occurred in anaplastic thyroid carcinoma (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…In order to test the impact of long-term T 3 exposure and heightened TRβ expression we measured a well-studied downstream effector, glycogen synthase kinase 3 beta (GSK3β) and its substrate glycogen synthase 1 (GYS1). GSK3β is a multi-substrate kinase and, importantly, is implicated in the progression of numerous cancers including ATC (25,26). We observed a modest increase in phosphorylated, and thus inactivated, GYS1 in the presence of T 3 and a marked increase of pGYS1 in the presence of both TRβ and T 3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In order to test the impact of long-term T 3 exposure and heightened TRβ expression we measured a well-studied downstream effector, glycogen synthase kinase 3 beta (GSK3β) and its substrate glycogen synthase 1 (GYS1). GSK3β is a multi-substrate kinase and, importantly, is implicated in the progression of numerous cancers including ATC (25,26). We observed a modest increase in phosphorylated, and thus inactivated, GYS1 in the presence of T 3 and a marked increase of pGYS1 in the presence of both TRβ and T 3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies using human triple negative breast cancer or thyroid carcinoma cell lines showed increased tumor cell proliferation and migration under JAM-A gene silencing (67,68). Transfection of a JAM-A plasmid to these cell lines impaired transendothelial migration and colony formation.…”
Section: Jam-a Manipulation In Cancer Modelsmentioning
confidence: 99%
“…Evidence from the literature suggest that circulating, soluble JAM-A could be used as a biomarker for the detection of some types of cancer, such as multiple myeloma (65) and head and neck squamous cell carcinoma (66). Although few studies show that JAM-A can be downregulated in tumor sites of metastatic breast (67) and anaplastic thyroid carcinoma tissues (68), high levels of JAM-A protein expression in tumor tissues have been correlated with poor prognosis in breast cancer (69) and nasopharyngeal carcinoma (70) patients.…”
Section: Jam-a Manipulation In Cancer Modelsmentioning
confidence: 99%
“…Migration and invasion abilities were assessed by wound healing and by Matrigel matrix assays, respectively, as previously described [38].…”
Section: Migration and Invasion Assaysmentioning
confidence: 99%
“…Cell cycle progression and cell death were determined by fluorescence-activated cell sorting (FACS) analysis using propidium iodide staining and an FC500 Cytometer (Beckman Coulter, Milan, Italy) as previously described [38].…”
Section: Flow Cytometrymentioning
confidence: 99%